HLA-G1 increases the radiosensitivity of human tumoral cells - Gallegos, Cristina Eugenia (2014)
Different molecules regulate the response of tumoral tissues to ionizing radiation. The objective of this work was to determine if HLA-G1 expression modulates the radiosensitivity of human tumoral cell lines. To this end, human melanoma M8 and human erythroleukemia K562 cell lines, with their correspondent HLA-G1 negative and positive variants, were gamma irradiated and the survival frequency was determined by clonogenic assay. The survival fraction of HLA-G1 expressing cells was around 60% of HLA-G1 negative cells. The generation of acidic vesicular organelles was higher in HLA-G1 positive cells. Apoptosis levels showed statistically significant differences only in K562 cells, whereas the variation in G2/M cycle progression was only significant in M8 cells. In addition, irradiation diminished cell-surface HLA-G1 and increased soluble HLA-G1 levels. Soluble HLA-G1 has no influence on cell survival in any cell line. In summary, we could demonstrate that HLA-G1 confers higher radiosensitivity to HLA-G1 expressing cells.